Synthesis and optical properties of poss‐based oxadiazole nanohybrids with three‐dimensional molecular conjugated structure. Issue 10 (24th December 2013) - Yan, Yongxin; Wang, Jun; Liu, Tianbao; Wang, Xin; Su, Xinyan; Feng, Yan
Abstract A series of oxadiazole‐containing molecular hybrid materials with three‐dimensional structure (P1–P3) was prepared by Heck reaction based on the octavinylsilsesquioxane. All resultant hybrid materials are soluble in common organic solvents and possess good film‐forming property. Their structures and properties were characterized and evaluated by FTIR, 1H‐NMR, 13C‐NMR, 29Si‐NMR, MALDI‐TOF, UV–vis, photoluminescence (PL), cyclic voltammetry, and elemental analysis (EA). The results showed that the substituted arm numbers of hybrids (P2 and P3) with pushing electron groups were efficiently controlled. Moreover, the hybrids possessed a steady blue emission and good electron‐injecting property in film. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40246.